THE ROLE OF THAI GOVERNMENT TOWARDS PROSTITUTION PROBLEM - Nureesan Maha (HI 15 UMY 457, 2015)
*457 This undergraduate thesis aims to address the problem of prostitution in Thailand, because it relate with the image of the country. Thailand as a country of famous about tourism and tourism is the best factor that will increase the number of prostitutions, because it lead the people around the world come to Thailand in various of the numbers. Nowadays, there are many factors that make people choose to be prostitutes, such as economic, social culture, and political. From this problem the government tries to do and solve it the different ways even also cooperate and signing the MOU with other neighboring country in other to catch the people who involve in the trafficking women to sell them in the brothels, and also the protect the victims from trafficking groups, for example Laos and Myanmar. Training the police and giving the knowledge to women to know well about the prostitution problem. Giving fund is also the way to support the officers to solve this problem. The government is not only cooperates with the government but they are cooperate with other NGOs, and UN as well.